Análisis semiótico del personaje Baltazar Ushca y la Ruta del Hielero en el imaginario social de la provincia de Chimborazo, periodo septiembre 2016 – febrero 2021. - Tierra Velastegui, Andrea Estefania (2023)
The current research carried out a semiotic analysis Baltazar Ushca from the community Cuatro Esquinas in Guano town and the Ruta del Hielero of Chimborazo under the theoretical foundations of Saussure and the social imaginary from the perspective of Cornelius Castoriadis. It gathers interviews with those who personify the object of study. The researcher proceeded to analyze the main characteristics such as clothing, accessories, speech, origin, and history, each of its meanings can analyze the character and the life story that characterizes him. In addition, it determined that this character arises from his daily activity, such as the extraction of ice from the snowy Chimborazo and his walk to that place, a tourist route called the Route of the Iceman. Currently, this character represents a historical and tourist icon. Semiotically, the analyzed aspects have a high load of cultural representation that belongs to the Chimboracenses, Guaneños, and the villagers of Cuatro Esquinas identity, enhancing the Ecuadorian culture and tradition worldwide. Taking into account one of the traditions that Baltazar Ushca has before ascending the snowy Chimborazo is to perform a ritual of respect, asking permission to Taita Chimborazo. The researchers analyzed flora and fauna found in the “Ruta del hielero”. Throughout the trajectory that is traversed to reach the ice mines, which is the place where Baltazar performs his work, there is a great variety of flora in this beautiful place, like Chuquiragua, Polylepis tree, Licopodios, and straw, among others. This route also has a great diversity of Andean fauna; within this group are the following species: blackbirds, hummingbirds, guarros, curiquingues, vicuñas. It makes the Andean culture a pleasant place where people can enjoy nature and discover the harmony that gives us the Pacha Mama, thus carrying a legacy that, in turn, was a daily sustenance for Baltazar.